1982
DOI: 10.2105/ajph.72.5.476
|View full text |Cite
|
Sign up to set email alerts
|

A survey of personal habits, symptoms of illness, and histories of disease in man with and without vasectomies.

Abstract: Using questionnaire information provided by 4,385 vasectomized and 13,155 matched, non-vasectomized men, we found no significant differences between them for a large number of symptoms and diseases, including those of the cardiovascular system. After taking into account differences in their marital status, past smoking habits, and physical activity at work, significant statistical associations of vasectomy with joint pain or swelling, back trouble, and a history of kidney or bladder infection persisted. Our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Vasectomized monkeys were reported to have a greater than normal incidence of atherosclerosis (Clarkson and Alexander, 19801, possibly due to immunologic changes. However, epidemiologic studies have not revealed an increased incidence of atherosclerosis or other serious diseases in men (Lepow and Crozier, 1979;Massey et al, 1984;Petitti et al, 1982;Walker et al, 1981), and a subsequent study in monkeys showed no effect of vasectomy on atherosclerosis (Clarkson et al, 1988). Neverthe-less, vasectomy-induced elevations in antisperm antibodies may affect the reproductive organs and/or fertility after vasovasostomy.…”
Section: Introductionmentioning
confidence: 99%
“…Vasectomized monkeys were reported to have a greater than normal incidence of atherosclerosis (Clarkson and Alexander, 19801, possibly due to immunologic changes. However, epidemiologic studies have not revealed an increased incidence of atherosclerosis or other serious diseases in men (Lepow and Crozier, 1979;Massey et al, 1984;Petitti et al, 1982;Walker et al, 1981), and a subsequent study in monkeys showed no effect of vasectomy on atherosclerosis (Clarkson et al, 1988). Neverthe-less, vasectomy-induced elevations in antisperm antibodies may affect the reproductive organs and/or fertility after vasovasostomy.…”
Section: Introductionmentioning
confidence: 99%
“…Such widespread application has stimulated interest in the effects of the operation and in its potential reversibility. Studies in animals raised concern about possible systemic vascular effects of the antisperm antibodies that are induced by vasectomy (Bigazzi et al, 1976;Anderson et al, 1983;Alexander and Clarkson, 1978;Clarkson and Alexander, 19801, but these reports were balanced by controlled epidemiological studies which found no increased incidence of serious diseases in vasectomized men (Goldacre et al, 1979;Walker et al, 1981;Petitti et al, 1982;Massey et al, 1984). In addition, a more recent study in monkeys showed no effect of vasectomy on development of atherosclerosis (Clarkson et al, 1988).…”
mentioning
confidence: 99%
“…Table 1 displays the basic characteristics of the 12 included studies. Moreover, 2 were cross-sectional, [ 19 , 25 ] 4 were case–control, [ 17 , 18 , 21 , 26 ] and 6 were retrospective cohort studies. [ 20 , 22 24 , 27 , 28 ] The publication years of the included studies ranged from 1981 to 2005.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 , 18 ] Furthermore, 6 studies were performed among the middle-aged and elderly populations, [ 17 24 , 26 28 ] but one study did not report this. [ 25 ] The follow-up length was from 1 to 36 years. In the included clinical trials, the sample sizes varied between 413 and 184,253 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation